2020
DOI: 10.3389/fimmu.2020.00359
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting the Elderly: Mandatory Age- and Minimal Histocompatibility Matching

Abstract: Worldwide over 40% of patients receiving renal replacement therapy (RRT) are aged 65 years or older, a number that is still increasing. Renal transplantation is the preferred RRT, providing substantial survival benefit over those remaining on dialysis, including the elderly. Only 3% of patients aged 65 years or older accepted on the waiting list actually received a kidney transplant offer within the Eurotransplant allocation region. To increase the chance for elderly to receive a timely kidney transplant, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 71 publications
1
32
0
2
Order By: Relevance
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high degree of HLA incompatibility between donor and recipient has been shown to predispose to development of de novo donor‐specific HLA antibodies (DSAs) as well as to reactivation of preformed DSAs (Dreyer & de Fijter, 2020; Foroutan et al., 2019; Mohan et al., 2012). This may lead to antibody‐mediated rejection and subsequently impair long‐term allograft survival (Mehra & Baranwal, 2016; Slavcev, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been proposed that a minimal degree of HLA matching (e.g. for HLA‐DR) should be introduced also for the Eurotransplant Senior Program in order to reduce the incidence of rejection episodes and thus the need for more intense immunosuppression, thereby diminishing excess mortality due to infection (Dreyer & de Fijter, 2020; de Fijter, 2009). This strategy could potentially represent a compromise between short waiting times, short cold ischaemia time and reduced risk of rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The immunostaining results showed that HLA-ABC expression remained barely detectable in all non-rejecting brains at any time point up to 12 wpt (Fig.S5C), and very few HLA-ABC positive cells could be occasionally identi ed if given much prolonged survival time(data from another experiment with immune-suppression). We also failed to detect HLA-DR expression ( Fig.S5C), which has long been strongly associated to transplant rejection 31 . Thus, the expressions of HLA-ABC and HLA-DR antigens retained a low level in vivo during our observation time window, and should not be responsible for initiation of the late-onset human cell rejection.…”
Section: Hla-abc Expression Was Not the Trigger For The Late-onset Rementioning
confidence: 78%
“…Indeed, after transplantation, he had to be admitted to the ICU on postoperative day seven due to urosepsis and suspected cardiac infarction. Infectious complications are common among old kidney recipients and have been shown to be their second most frequent cause for DWFG [ 16 ]. In our cohort, 3 out of 17 (17.6%) patients had to be admitted to the ICU because of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The Eurotransplant Senior Program (ESP) is a special kidney transplant program which was initiated in 1999 to reduce waiting times by allocating kidneys from deceased donors aged ≥65 years to old recipients aged ≥65 years. Before that date, only 3% of patients aged 65 years or older actually received a KT offer within the Eurotransplant region, because younger patients with more favorable outcomes were prioritized [ 16 ]. In ESP, organ allocation is not based on immunological compatibility, but on local, regional or national allocation and AB0-compatibility, in order to reduce cold ischemia time (CIT).…”
Section: Introductionmentioning
confidence: 99%